1994
DOI: 10.1002/jso.2930570406
|View full text |Cite
|
Sign up to set email alerts
|

Practical management of post-thyroidectomy hematoma

Abstract: Thyroid diseases and surgery for thyroid neoplasms are both very common. Several complications of thyroidectomy are well known. Some of these are quite disturbing, such as recurrent laryngeal nerve injury and permanent hypoparathyroidism. However, postoperative hematoma often in the recovery room may be fatal. Close observation and early intervention are of utmost necessity in the post-thyroidectomy period. In a series of 600 thyroidectomies performed over a period of 11 years, eight patients developed postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
123
3
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 8 publications
11
123
3
2
Order By: Relevance
“…Previous studies established that the greatest risk of respiratory failure caused by hematoma occurs during the first 6 h after thyroid surgery and this result disencourages the discharging of the patients on the day of the operation (Hurtado-López et al, 2001;Matory and Spiro, 1993;Shaha and Jaffe, 1994). In the present study, developed two hematomas were minimal and possibly developed over a long time.…”
Section: Resultssupporting
confidence: 56%
“…Previous studies established that the greatest risk of respiratory failure caused by hematoma occurs during the first 6 h after thyroid surgery and this result disencourages the discharging of the patients on the day of the operation (Hurtado-López et al, 2001;Matory and Spiro, 1993;Shaha and Jaffe, 1994). In the present study, developed two hematomas were minimal and possibly developed over a long time.…”
Section: Resultssupporting
confidence: 56%
“…[1][2][3] While a variety of factors (eg postoperative hypertension, use of anticoagulants and extent of dissection) have been implicated in increasing the risk of post-thyroidectomy haemorrhage, it is generally considered a low frequency stochastic event, which is difficult to predict. [4][5][6][7] Bleeding deep to the strap muscles is associated with a higher risk of life threatening airway swelling and obstruction, and the risk of post-thyroidectomy haemorrhage is highest in the early hours following surgery. 8 For these reasons, patients traditionally remained in hospital for 72 hours or longer after thyroidectomy.…”
mentioning
confidence: 99%
“…2,9,11,12,14 Two large nonrandomized studies of 250 and 400 patients have also documented that no benefits of using the drains in thyroid surgery. 15,17 Author found that drain was containing fluid even in the absence of collection in thyroid bed by ultrasonography. The reason for this may be an inflammatory effect of drain itself and effect of suction which prevents lymphatic channels from sealing off.…”
Section: Discussionmentioning
confidence: 99%
“…Though this complication is rare, ranging from 0.3 to 2.5%. [14][15][16] This serious complication most of the time appears between 2 to 6 hours post-operatively and many patients complain coughing just before hemorrhage. Possible causes for this are slippage of an improperly applied suture and improperly cauterized area.…”
Section: Discussionmentioning
confidence: 99%